PENGARUH KEEFEKTIFAN TRAFFIC LIGHT PADA SIMPANG BERSINYAL SIMPANG SURABAYA - Muhammad Rico Salianto; Heru Pramanda; Bunyamin Bunyamin (Universitas Teuku Umar, 2021)
Banda Aceh has unavoidable transportation problems, such as congestion on a number of roads. One of the areas with a fairly high level of congestion and becoming the center of attention is the Simpang Surabaya area, so the Aceh Government decided to build a traffic light at the Simpang Surabaya to prevent congestion and travel delays. The purpose of this study was to review the effectiveness after the presence of a traffic light which includes the performance of the road network and to determine the vehicle speed profile at the crossroads under review. The method used is the 1997 Indonesian Road Capacity Manual. The results obtained are the highest vehicle volume occurs on Monday at the peak hour of the highest vehicle at 07.00 - 08.00 WIB and 08.00 - 09.00 WIB on T. Hasan Dek road at 14976 Kend/hour . The results of calculations using the 1997 MKJI method obtained a total cycle time of 134 seconds and a yellow time of 3 seconds consisting of the T. Hasan Dek road with a red time of 44 seconds, and a green time of 90 seconds, while on the M. Hasan road for a red time of 83 seconds. , and the green time is 50 seconds. On the T. Imuem Lueng Bata road, the red light setting is 99 seconds and the green light is 35 seconds, and on the T. Chik Ditiro road, the red light is 110 seconds and the green time is 24 seconds.Keywords : Performance of Signalized Intersection, MKJI 1997